The Parent-Coach/Child-Athlete Relationship in Youth Sport: Cordial, Contentious, or Conundrum? - Weiss, M. R.; Fretwell, S. D. (Research Quarterly for Exercise and Sport, 2005)
The roles of coach and parent are often synonymous in youth sport, but little data-based research has been conducted on the parent-coach/child-athlete relationship. Six boys in U-12 competitive soccer were interviewed regarding positive and negative aspects about playing for their father-coach. Similar questions were posed to father-coaches and two teammates. Inductive content analysis indicated that, among the benefits, sons identified perks, praise, technical instruction, understanding of ability level, insider information, involvement in decision making, special attention, quality time, and motivation. Costs of being coached by one`s father included negative emotional responses, pressure/expectations, conflict, lack of understanding/empathy, criticism for mistakes, and unfair behavior. For father-coaches, positive themes included taking pride in son`s achievements, reason for coaching, positive social interactions, opportunity to teach skills and values, enjoying coaching son, and quality time. Negatives included inability to separate parent-child from coach-player role, placing greater expectations and pressure on son, and showing differential attention toward son. While teammates perceived some favoritism by the parent-coach, they cited mostly positive instructional experiences. Results are discussed within motivational theories that highlight the influence of significant adults on children`s psychosocial development in the physical domain.